Identity and regional development - Rozas, Germán (Revista de Psicología, 1997)
Being the subject of identity an important object of study for psychology, paradoxically it has not been profusely investigated, especially in recent years, especially in the social area. And it is precisely interesting to locate this concept here in the field of population development, of communities, of communes. Said more directly, in the context of the regional. The Chilean State has targeted the regions of our country, an attitude that indicates the need, even for a moment, not to privilege the center. This article intends to show this process, fundamentally describing some aspects of the regional reality and, at the same time, observing the configuration of identity. It ends by complementing with the contribution of action and change mechanisms such as territorial management and intersectoriality.